2015
DOI: 10.1182/blood-2014-04-566778
|View full text |Cite
|
Sign up to set email alerts
|

Global microRNA expression profiling uncovers molecular markers for classification and prognosis in aggressive B-cell lymphoma

Abstract: Key Points Well-defined miRNA signatures for normal B-cell subsets and their malignant counterparts including BL and DLBCL subgroups were identified. In DLBCL, miRNA-155 expression is associated with R-CHOP resistance, but in vitro sensitivity to AKT pathway inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
105
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 49 publications
10
105
3
Order By: Relevance
“…Their miR-155 expression levels were 33.0, 30.0 and 17.0. Also, another BL case with miR-155 expression level of 26.0 was died after the first cycle of therapy which was consistent with previous study performed by Iqpal et al [38]. These findings mean that miR-155 does not act as tumor suppressor gene in BL because of the bad prognosis that accompanying BL cases who were expressing increased levels of miR-155.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their miR-155 expression levels were 33.0, 30.0 and 17.0. Also, another BL case with miR-155 expression level of 26.0 was died after the first cycle of therapy which was consistent with previous study performed by Iqpal et al [38]. These findings mean that miR-155 does not act as tumor suppressor gene in BL because of the bad prognosis that accompanying BL cases who were expressing increased levels of miR-155.…”
Section: Discussionsupporting
confidence: 89%
“…Their mean fold-change values had spanned from 3 to 19 in patients with DLBCL [29][30][31][32][33][34][35][36][37]. As well, a lot of studies have found down regulation of miR-155 expression levels within BL versus CLL, MCL and FL [38,39]. Contrary, the studies of Eis et al [40] and Metzler [41] showed that miR-155 was up-regulated in pediatric burkitt's lymphoma which is opposite to what was shown in ours.…”
Section: Discussioncontrasting
confidence: 71%
“…Other studies have shown these microRNAs to be regulated by the Myc, Bcl-6, STAT3, and NF-κB pathways, and the MIR17HG locus was frequently amplified in Burkitt lymphoma. [45][46][47][48] Downregulation of MIR155HG expression may contribute to the pathogenesis of MYC translocation, as miR-155 suppresses activation-induced cytidine deaminase, which mediates MYC/IGH translocation. 49 These microRNA signatures may also be implicated in defining the gene expression profiling features of MYC-R + /Myc high GCB-DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…In lymphoma cells, ectopic expression of miR-155 is associated with downregulation of IGJ, FAS, SMAD3/5, and BACH1, as well as HLA genes. 45 IGJ, FAS, and genes involved in BMP/SMAD pathways (such as SMAD1, BMP3, and BMP7), as well as SMARCA4 (miR-21 target gene 50 ), were upregulated in MYC-R + GCB-DLBCL (Tables 3 and 5). miR-155 target gene BCL2 showed increased Bcl-2 protein expression in ABC-DLBCL (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…A four-microRNA signature comprising miR-486, miR-30d, miR-1 and miR-499 in the serum independently predicts survival of non-small cell lung cancer, showing potential of microRNAs as noninvasive prognosis predictor [85]. In a recent study, high expression levels of miR-155 were significantly associated with therapeutic resistance of patients with diffuse large B-cell lymphoma to the rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone treatment [86]. These microRNA indicators for therapeutic response may help stratify patients for anticancer treatment to avoid unnecessary treatments.…”
Section: Potential Use Of Microrna As Cancer Biomarkersmentioning
confidence: 99%